Response to: Traynor et al. "Assessing eye orbits as predictors of Neandertal group size". - Dunbar, R; Pearce, E; Stringer, C (Wiley, 2015)
We are somewhat concerned by the number of errors and misconceptions in Traynor et al.’s (2015) comment on our paper (Pearce et al. 2013) in which we argue that Neanderthal brain structure must have been sufficiently different to that of anatomically modern humans to have had significant consequences for the sizes of their communities and key social cognitive abilities.